The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10856-012-4680-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-centered radicals in γ-irradiated bone substituting biomaterials based on hydroxyapatite

Abstract: Gamma irradiated synthetic hydroxyapatite, bone substituting materials NanoBone(®) and HA Biocer were examined using EPR spectroscopy and compared with powdered human compact bone. In every case, radiation-induced carbon centered radicals were recorded, but their molecular structures and concentrations differed. In compact bone and synthetic hydroxyapatite the main signal assigned to the CO(2) (-) anion radical was stable, whereas the signal due to the CO(3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Despite the differences, signal II is perhaps related to the CO 2 radical while signal I is potentially associated with a trapped free electron in the material matrix. These results are in agreement with several other studies performed on similar materials following irradiation by ESR analysis (Chróścicka et al, 2016;MatkoviA et al, 2012;Sadlo et al, 2012). Sample G36P24 displayed a notable decrease in the intensity of the signals in particular signal I, suggesting that the annealing step for 24 hours reduced the free radicals generated.…”
Section: Esrsupporting
confidence: 92%
“…Despite the differences, signal II is perhaps related to the CO 2 radical while signal I is potentially associated with a trapped free electron in the material matrix. These results are in agreement with several other studies performed on similar materials following irradiation by ESR analysis (Chróścicka et al, 2016;MatkoviA et al, 2012;Sadlo et al, 2012). Sample G36P24 displayed a notable decrease in the intensity of the signals in particular signal I, suggesting that the annealing step for 24 hours reduced the free radicals generated.…”
Section: Esrsupporting
confidence: 92%
“…For irradiated samples, the main stable component can be assigned to CO − 2 . In previous studies [60][61][62][63][64][65][66][67], it was shown that the EPR spectra of biological, as well as synthetic carbonated calcium apatites, exhibit a complex EPR signal at around g = 2, which comprises several powder spectrum contributions arising from different paramagnetic species (CO − 3 , CO 3− 3 , CO − 2 , O − 3 , O − ) stabilized in different locations (at hydroxyl, phosphate or surface sites) or from the same species, recognized by the difference in g anisotropy. However, as the EPR spectra of apatite are strongly dependent on the conditions of sample preparation (CO 2 flow, drying temperature, annealing procedure, etc.)…”
Section: Influence Of Amino Acids On the Properties Of Formed Capsmentioning
confidence: 99%